Antifungal susceptibility pattern of Candida auris strains - Kübra Evren; Beyza Öncel; Selda Kömeç (Journal of Global Antimicrobial Resistance)
AIM: To report findings of the MIC values of Candida auris isolates November 2020 to July 2024. BACKGROUND: Candida auris has become a global concern because of its association with nosocomial outbreaks and resistance to antifungals. Due to its importance we investigated the antifungal susceptibilities of C. auris isolates from various clinical samples. METHODS: Patients with colonization or infection with C. auris between November 2020 and July 2024 were included. Strains were identified by MALDI-TOF MS. Antifungal susceptibility tests were evaluated by Sensititre YeastOne (Thermofisher, UK). RESULTS: Of the 270 C. auris isolates, 156 were isolated from screening culture, 48 from urine, 38 from blood, 14 from catheters, eight from tracheal aspirates, five from wounds and one from tissue samples. Of the patients from whom C. auris was isolated, 53.7% were male and 46.3% were female, and the age range was 1-101 (mean: 58.5). The proportion of patients hospitalized in the ICU was found as 83.2%. For 90 isolates antifungal susceptibility tests were perfomed. The MIC ranges, MIC50, and MIC90 values obtained for nine antifungals are given in Table 1. One isolate was resistant to fluconazole, amphotericin B and echinocandins. According to CDC criteria, fluconazole resistance was determined as 84.4% and amphotericin B as 16.6%. CONCLUSION: Due to high resistance rates and the rapid dissemination of Candida auris, it is crucial to quickly determine antifungal susceptibility results. This is important because C. auris causes infections with high mortality and morbidity, and prompt antifungal management can significantly impact patient outcomes.